2021
DOI: 10.2147/pgpm.s286717
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of PD-L1 Non-Coding Polymorphisms on the Prognosis of a Genetically Admixed NSCLC Cohort

Abstract: Purpose Although non-small cell lung cancer (NSCLC) remains a deadly disease, new predictive biomarkers have emerged to assist in managing the disease, of which one of the most promising is the programmed death‐ligand 1 (PD-L1). Each, PD-L1 variant seem to modulate the function of immune checkpoints differently and affect response to adjuvant treatment and outcome in NSCLC patients. We thus investigated the influence of these PD-L1 genetic variations in genetically admix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…Yeo and his colleagues reported that the PD‐L1 rs4143815 GG genotype may be beneficial for predicting poor prognosis in lung adenocarcinoma as patients with this genotype had lower overall survival and disease-free survival compared to patients with other genotypes of PD-L1 rs4143815 [ 27 ]. As well, prior studies stated that the PD‐L1 rs4143815C > G was significantly associated with a worse survival outcome and relapse with NSCLC and breast cancer [ 10 , 28 , 29 ]. Furthermore, Lee et al [ 30 ] investigated whether the PD-L1 gene polymorphisms could predict the clinical outcome of patients with advanced NSCLC after paclitaxel-cisplatin chemotherapy and they found that the rs4143815 CG SNP was significantly associated with a better response under additive model for the G-allele.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Yeo and his colleagues reported that the PD‐L1 rs4143815 GG genotype may be beneficial for predicting poor prognosis in lung adenocarcinoma as patients with this genotype had lower overall survival and disease-free survival compared to patients with other genotypes of PD-L1 rs4143815 [ 27 ]. As well, prior studies stated that the PD‐L1 rs4143815C > G was significantly associated with a worse survival outcome and relapse with NSCLC and breast cancer [ 10 , 28 , 29 ]. Furthermore, Lee et al [ 30 ] investigated whether the PD-L1 gene polymorphisms could predict the clinical outcome of patients with advanced NSCLC after paclitaxel-cisplatin chemotherapy and they found that the rs4143815 CG SNP was significantly associated with a better response under additive model for the G-allele.…”
Section: Discussionmentioning
confidence: 88%
“…rs2297136 is found in the 3′-UTR of PD-L1 gene and serves as a binding site for miRNA-324-5p, miRNA‐632, and miRNA-296-5p. An A to G change, at this location, has been shown to enhance the binding power between PD-L1 mRNA and its regulatory miRNAs resulting in a decline of PD-L1 gene transcription and protein expression [ 10 , 20 ]. The results of the current study indicated that rs2297136 (A > G) AA genotype was significantly associated with the development of liver cirrhosis but not with HCC development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies from the present case series have shown that Brazilian patients represent a genetically admixed NSCLC cohort with clinical implications. In fact, we found that patients with adenocarcinoma harboring somatic mutations of EGFR , CTLA4 , PDCD1LG2 , or ZEB2 that only underwent surgical treatment and developed brain metastases may have the worst prognosis ( 8 , 9 ). EGFR somatic mutations were detected in approximately 13% of NSCLC Brazilian patients with clinical significance to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies performed by our group using frozen tissue specimens and next-generation sequencing (NGS) from a cohort of 70 patients have shown that Brazilian patients represent a genetically admixed NSCLC cohort with important predictive and prognostic implications ( 8 , 9 ). In the same case series and the array used (QIAamp DNA Mini Kit Qiagen), we detected some Brazilian patients with NSCLC harboring rare EGFR variants with clinical significance to be defined.…”
Section: Introductionmentioning
confidence: 99%